“What Makes a Good Class?” - Assessing University Students and Teachers’ Perceptions - MOURA, Ana; GOMES, Carolina; JACQUES, Teresa; MACEDO, Eunice; MARTINS, Mariana Veloso (Journal of Research in Educational Sciences; Vol 16 No 2 (2025): JRES, Volume XVI, Issue 2(20), Winter 2025, 2025)
This study explores the perceptions of university students, teachers, and researchers on what constitutes a ‘good class’ in higher education. Using qualitative data from 733 participants at a large Portuguese public university, the study applies Bronfenbrenner’s ecological model to identify three key systems influencing these perceptions: microsystem, mesosystem, and exosystem. The microsystem highlights the importance of student-teacher interactions, teaching skills, and student engagement. The mesosystem emphasizes pedagogical methods, advocating for interactive and innovative teaching approaches, while the exosystem focuses on structural factors like class size and facilities. The findings reveal the critical role of these systems in shaping class quality, offering insights for improving higher education by aligning teaching practices with the expectations of students and educators. The study also calls for pedagogical innovation to address contemporary challenges and meet diverse student needs, providing valuable guidance for educators and policymakers.